2020
DOI: 10.1097/bsd.0000000000000945
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Assessment Using an Endoscopic Scoring System for Early and Persistent Dysphagia After Anterior Cervical Decompression and Fusion Surgery

Abstract: Study Design: Prospective study. Objectives: Preoperative and postoperative dysphagia was evaluated by an otolaryngology doctor and a speech-language-hearing therapist using the eating assessment tool (EAT-10) and Hyodo-Komagane scores. The objective was to achieve a more precise evaluation of the incidence and risk factors of early and persistent dysphagia after anterior cervical discectomy and fusion (ACDF). Summary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This test has utility in otolaryngology and has been validated for the evaluation of dysphagia and detection of the risk of aspiration pneumonia 12,13) . Our recent study demonstrated that evaluation of preoperative dysphagia, by an otolaryngologist and a speech-language-hearing therapist, using EAT-10 and FEES is useful for predicting the incidence and risk factors of postoperative dysphagia after ADF 14) .…”
Section: Introductionmentioning
confidence: 99%
“…This test has utility in otolaryngology and has been validated for the evaluation of dysphagia and detection of the risk of aspiration pneumonia 12,13) . Our recent study demonstrated that evaluation of preoperative dysphagia, by an otolaryngologist and a speech-language-hearing therapist, using EAT-10 and FEES is useful for predicting the incidence and risk factors of postoperative dysphagia after ADF 14) .…”
Section: Introductionmentioning
confidence: 99%
“…However, dysphagia is one of the most common complications affecting recovery. 2,3,5,6 LSA to decrease dysphagia after ACDF is considered a meaningful method, but the safety and efficacy still exist in controversy. The present study conducted a systematic review and meta-analysis of the available literature and the result found that LSA may be an effective therapy to reduce the rate and severity of dysphagia after ACDF and mitigate PSTS in the early postoperative period without increasing early steroid-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 Meanwhile, dysphagia is one of the most common ad.verse events associated with ACDF, especially in the early postoperative period. [2][3][4] Dysphagia not only results in adverse psychological consequences and increased possibility of other complications (fluid/electrolyte disorders, aspiration, etc) but also leads to longer hospitalization time and increased financial burden. 5,6 Although several risk factors of dysphagia including female, sex, revision surgery, longer surgery time, multilevel fusion, use of rhBMP-2, cervical plate type and position, preexisting neck pain, and smoking have been determined, local soft-tissue swelling is also one of the most common reasons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Ohba et al used the EAT-10 and the Hyodo-Komagane score with endoscopic evaluation to assess risk factors for postoperative dysphagia after ACDF. This study found that aging and smoking were risk factors for transient dysphagia [ 22 ]. Other studies have found risk factors for dysphagia after ACDF to include aging, operation time, blood loss, smoking, endocrine disorders, and an increased number of upper cervical spine surgeries [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%